PENGARUH MODEL PROBLEM BASED LEARNING (PBL) DENGAN PENDEKATAN DIFERENSIASI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI PERUBAHAN WUJUD BENDA KELAS IV SD SANTO THOMAS 2 MEDAN - Sinaga, Roberta Repina Hartati; Nova Florentina Ambarwati; Ester Julinda Simarmata; Juliana; Dyan Wulan Sari HS; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model with a differentiated learning approach on students’ critical thinking skills in Science and Social Studies (IPAS) on the topic of Changes in States of Matter in Grade IV of SD Santo Thomas 2 Medan in the 2025/2026 academic year. The study was motivated by the low level of students’ critical thinking skills, as indicated by learning outcomes that had not yet reached the Minimum Learning Achievement Criteria and by teacher-centered instructional practices. This research employed a quantitative approach using a Quasi-Experimental Design with a Nonequivalent Control Group Design. The sample consisted of 24 students in the experimental class (IVB) and 24 students in the control class (IVA). Data were collected through tests, questionnaires, observations, and documentation. Data analysis included normality testing, homogeneity testing, Independent Sample t-Test, and N-Gain analysis. The findings revealed that the posttest mean score of the experimental class was 73.31, higher than that of the control class at 62.71. The hypothesis test showed a significance value (Sig. 2-tailed) of 0.001 < 0.05, indicating that H₀ was rejected and Ha was accepted. The N-Gain score of the experimental class was 0.60, categorized as moderate, with an effectiveness level of 60.46% (fairly effective). In addition, the questionnaire results showed an average score of 83.11, categorized as very good. Therefore, the Problem Based Learning (PBL) model with a differentiated learning approach has a significant effect on improving students’ critical thinking skills in IPAS learning.